2016
DOI: 10.1515/zpch-2015-0703
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Ce:YAG Amount on Structure and Optical Properties of Ce:YAG-PMMA Composites for White LED

Abstract: Ce:YAG-poly(methyl methacrylate) (PMMA) composites were prepared by using a melt compounding method, adding several amounts of Ce:YAG in the range 0.1-5 wt. %. The optical properties of the obtained composites and of the composites combined with a blue LED were measured to investigate the effect of the amount of Ce:YAG on the resulting emitted light in view of possible application in white LED manufacture. An increase in Ce:YAG amount caused an increase in the emission and a shift of 15 nm, influencing the whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Further solid-state NMR tests showed that the addition of Ce:YAG particles strongly influenced the T 1ρ (C) values. The change in relaxation time demonstrates that electron donor interactions occur between the carboxy-oxygen lone pair and the surface yttrium or cerium ions, resulting in a shift in the emission spectrum and a more homogeneous composite [92]. The same phenomenon was observed in composites formed by the doping of the rare earth organic complex Eu(TTA) 3 (H 2 O) 2 (TTA: thenoyltrifluoroacetone) in poly(ethylene oxide) (PEO), where the luminescence position of the composite shifted with the change in the molar ratio of the complex to the polymer [93].…”
Section: Strategy For Activating Ion Concentration and Phosphors Conc...mentioning
confidence: 99%
“…Further solid-state NMR tests showed that the addition of Ce:YAG particles strongly influenced the T 1ρ (C) values. The change in relaxation time demonstrates that electron donor interactions occur between the carboxy-oxygen lone pair and the surface yttrium or cerium ions, resulting in a shift in the emission spectrum and a more homogeneous composite [92]. The same phenomenon was observed in composites formed by the doping of the rare earth organic complex Eu(TTA) 3 (H 2 O) 2 (TTA: thenoyltrifluoroacetone) in poly(ethylene oxide) (PEO), where the luminescence position of the composite shifted with the change in the molar ratio of the complex to the polymer [93].…”
Section: Strategy For Activating Ion Concentration and Phosphors Conc...mentioning
confidence: 99%
“…In recent years, great interest in nanomaterials has been observed due to their enormous potential in fundamental studies and the technological field. In this broad class of nanomaterials, an important role is played by luminescent nanoparticles and, in particular, by those activated by trivalent lanthanide ions, due to their promising applications in the fields of bioimaging, lighting, optical nanothermometry, and solar concentrators. …”
Section: Introductionmentioning
confidence: 99%